Dual pH and temperature responsive hydrogels based on β-cyclodextrin derivatives for atorvastatin delivery. (20th January 2016) - Yang, Kaiwen; Wan, Sicheng; Chen, Binbin; Gao, Wenxia; Chen, Jiuxi; Liu, Miaochang; He, Bin; Wu, Huayue
Highlights: A dual pH and temperature responsive hydrogel was fabricated. The swelling behavior of the hydrogel was investigated. The release profiles of atorvastatin from the hydrogel were studied. The solubility of atorvastatin was improved greatly in the hydrogel. Abstract: 2-Methylacrylic acid modified β-cyclodextrin was copolymerized with 2-methylacrylic acid and N, N′-methylene diacrylamide to fabricate dual pH and temperature responsive hydrogels for the controlled release of atorvastatin. The swelling behaviors, pH and temperature responsive atorvastatin release profiles of the hydrogels were investigated. The results indicated that the hydrogel prepared in DMSO exhibited the best swelling rate, which was 51 for 10 min and 252 for 16 h when immersed in medium of buffer solution with pH = 8.06. The media with low (pH ≤ 3.84) and high (pH ≥ 10.34) pH values would reduce the swelling rate of hydrogels. The swelling of the hydrogel was increased with increasing temperature from 30 °C to 45 °C. Atorvastatin was loaded in the hydrogel for drug release investigation. The cumulative release rate of atorvastatin was as high as 90.5% in pH = 8.06 buffer solution. The solubility of atorvastatin was improved from 0.13 to 1.2 mg/mL in the hydrogel.